A blended approach in teaching an EAP course: Malaysian instructors’ perceptions of the new course materials - Wong, Fook Fei; Thang, Siew Ming; Hafizah Latif,; Mohd Sallehhudin Abd. Aziz,; Noorizah Mohd Noor, (Pusat Pengajian Bahasa dan Linguistik, FSSK, UKM, 2012)
This paper reports on a study which examines instructors’ perceptions of the new commercial course materials that comprises a course book and online practice reinforcement activities. The materials were used to teach undergraduate English for Academic Purposes (EAP) course for Social Sciences at a Malaysian public university. This represents the main facet of the blended approach introduced when the course was redesigned. The sample comprises ten instructors who taught the course for one semester. Three qualitative instruments were utilized to elicit data namely, instructor-researcher reflective notes, focus group discussion and one-to-one interviews. The results of the study were generally positive, however, two main concerns were raised. The first was regarding the difficulty level of the reading comprehension activities in the course book which majority of the instructors felt were too simple and not challenging enough for their students. The second was on internet connectivity to the online practice website which the instructors felt was too slow and was unable to support the students efficiently. The paper concludes by discussing the implications of the findings and provides suggestions for the next cycle of the research